Neo-Victorianism, Feminism, and Lace: Amy Atkin's Place at the Dinner Table. (2nd October 2021) - Quarini, Carol
Abstract: This practice-based, interdisciplinary research focuses on the life and work of Amy Atkin, who claimed to be the first female Nottingham machine-lace designer. This study contextualizes her work within the framework of other early female British art students. Constrained by domesticity, like many other middle-class women in the early twentieth century, she had to relinquish paid work on marriage. The waste of talent resulting from this requirement inspired a practice response, based on table mats, informed by Amy Atkin's lace designs, Catherine Bertola's 2008 exhibition Prickings, and Judy Chicago's iconic second-wave feminist work The Dinner Party (1979). This use of domestic textiles to critique gender politics and thus to subvert the quotidian is discussed and the theory of neo-Victorianism is used to consider works by textile artists who use the life of Victorian women as inspiration for practice that critiques feminism through the lens of the twenty-first century. This research combines social history, feminism, neo-Victorianism, and subversive stitching to consider the continuing constraints of domesticity on women's lives both in the early twentieth and twenty-first centuries.